Organic-inorganic photosensor controlled by frequency based on nanostructure 1,4-diaminoanthraquinone and p-silicon - Yakuphanoğlu, Fahrettin; Farooq, W. Aslam (Elsevier Science Sa, 2011)
The electrical and photosensing properties of the p-Si/1,4-DAAQ inorganic-organic diode have been investigated. The diode exhibits a non-ideal behavior with ideality factor of 2.03 and barrier height of 0.85 eV. The photovoltaic parameters, open circuit voltage, V-oc and short circuit current, I-sc of Al/p-Si/1,4-DAAQ diode under AM1.5 were found to be V-oc = 0.365 V and I-sc = 127 mu A, respectively. The interface state density of the diode can be controlled by the illumination. The ratio values of C-photo/C-dark under 10 kHz, 100 kHz and 500 kHz spot frequencies were found to be 3.73, 3.33, 1.70 and 1.02, respectively and the C-photo/C-dark values decrease with increasing frequency. The obtained results indicate that the photocapacitance properties of the Al/p-Si/1,4-DAAQ diode can be controlled by frequency. It is evaluated that this device can be used a photosensor controlled frequency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Organic semiconductor; Photodiode; Photovoltaic